2019
DOI: 10.1080/07900627.2019.1585764
|View full text |Cite
|
Sign up to set email alerts
|

Understanding emergent participation practices in water governance

Abstract: This introductory article discusses the proliferation of different forms of participation in water governance. It is argued that creating public value through participation can only succeed when effective cocreation between public authorities and communities emerges. However, challenges to realizing co-creation are manifold, and differ among the various types of participation. In this respect, we introduce a typology of different forms of participation, based on the distinction between top-down (invited) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…Thus, it can be concluded that currently employed drought and water scarcity management options in England and Wales rely significantly on restricting water use in times of drought and are therefore, with the exception of elements of drought plans and WRMPs, potentially too focused on thinking about water scarcity in the context of actual drought events. Given the large number of drought and water scarcity management options identified in the literature review that focus on proactive measures such as the ones represented in the "Valuing water/ attitudes" box or "Land use planning" box, English and Welsh water companies are missing out on current trends in drought and water scarcity 3 Water Resources Management Plans (Dee Valley Water, 2013;Peel Water Networks, 2013;Affinity Water, 2014;Anglian Water, 2014;SSE Water, 2014a;Bristol Water, 2014;SSE Water, 2014b;Cambridge Water, 2014;Cholderton and District Water, 2014;Essex and Suffolk Water, 2014;Northumbrian Water, 2014;Portsmouth Water, 2014;SES Water, 2014;Severn Trent, 2014;South East Water, 2014;South Staffs Water, 2014;South West Water, 2014;Southern Water, 2014;Thames Water, 2014;Veolia Water Projects, 2014;Welsh Water, 2014;Wessex Water, 2014;Yorkshire Water, 2014;Sembcorp Bournemouth Water, 2015; United Utilities, 2015) management that could potentially be beneficial and shift the emphasis away from measures that are too focused on thinking about water scarcity in the context of actual drought events.…”
Section: Current Drought and Water Scarcity Management Options In England And Walesmentioning
confidence: 99%
“…Thus, it can be concluded that currently employed drought and water scarcity management options in England and Wales rely significantly on restricting water use in times of drought and are therefore, with the exception of elements of drought plans and WRMPs, potentially too focused on thinking about water scarcity in the context of actual drought events. Given the large number of drought and water scarcity management options identified in the literature review that focus on proactive measures such as the ones represented in the "Valuing water/ attitudes" box or "Land use planning" box, English and Welsh water companies are missing out on current trends in drought and water scarcity 3 Water Resources Management Plans (Dee Valley Water, 2013;Peel Water Networks, 2013;Affinity Water, 2014;Anglian Water, 2014;SSE Water, 2014a;Bristol Water, 2014;SSE Water, 2014b;Cambridge Water, 2014;Cholderton and District Water, 2014;Essex and Suffolk Water, 2014;Northumbrian Water, 2014;Portsmouth Water, 2014;SES Water, 2014;Severn Trent, 2014;South East Water, 2014;South Staffs Water, 2014;South West Water, 2014;Southern Water, 2014;Thames Water, 2014;Veolia Water Projects, 2014;Welsh Water, 2014;Wessex Water, 2014;Yorkshire Water, 2014;Sembcorp Bournemouth Water, 2015; United Utilities, 2015) management that could potentially be beneficial and shift the emphasis away from measures that are too focused on thinking about water scarcity in the context of actual drought events.…”
Section: Current Drought and Water Scarcity Management Options In England And Walesmentioning
confidence: 99%
“…Commonly, there are two kinds of participation model, top-down and bottom-up. The top-down approach is a participation model which is derived from government programs and related to policy implementation [23]. Top-down approach recognizes the value of people's involvement in water management [24].…”
Section: Top Down and Bottom Up Approachmentioning
confidence: 99%
“…It is triggered by a controversial policy process initiated by public authorities responding to specific needs in the local community. In bottom-up initiatives, local partners become vital for governments in planning, management, and also implementation processes, including operation and maintenance [23]. Thus, government and community should have an equal relationship to develop the governance capacity to solve public issues effectively and transparently [23].…”
Section: Top Down and Bottom Up Approachmentioning
confidence: 99%
See 2 more Smart Citations